Putting Stress in Historical Context: Why It Is Important That Being Stressed Out Was Not a Way to Be a Person 2,000 Years Ago - Hutmacher, Fabian (Frontiers in Psychology, 2021)
It was not until the middle of the 20th century that scientists and Western societies began to label the combination of physiological and psychological responses that people display when things are getting too much and out of balance as ‘stress’. However, stress is commonly understood as a universal mechanism that exists across times and cultures. In a certain sense, this universality claim is correct: The physiological and endocrinological mechanisms underlying the stress response are not a modern invention of our body. In another sense, the universality claim is potentially problematic: Stress has become, but has not always been, a way to be a person. That is, the social practices in which the physiological and endocrinological stress mechanisms are embedded, are not the same across times and cultures. Crucially, these social practices are not a negligible by-product, but form an essential part of the way stress is commonly understood and experienced. Against this background, one may still decide to use the word ‘stress’ when speaking about other times and cultures. Nevertheless, one should at least be cautious when doing so for three reasons. First, using the word ‘stress’ when referring to societies different from our own may create the impression of a similarity between then and now, which does not actually exist. Second, it may blind us to the nature of the differences between times and cultures. Third, it naturalizes a contemporary scientific concept, which is more adequately viewed as the result of complex social, historical, and societal processes. Putting the stress concept in historical context and acknowledging that its use emerged in a specific historical environment enables us to take a step back and to think about the ways that stress shapes our lives. In other words, viewing stress as a culture-bound concept can give us the possibility to reflect upon our modern societies, in which the concept emerged.